PENGARUH POLA ASUH ORANGTUA TERHADAP KENAKALAN REMAJA DIKELURAHAN REJOSARI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Windi Fitrianti; Gimin Gimin; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research occurred because by the increasing a number of teenagers who were suspected of being involved in the symptoms of juvenile delinquency in the Kelurahan Rejosari Kecamatan Tenayan Raya Kota Pekanbaru, the example of juvenile delinquency like smoking, ride reckless motorcycle and etc. vina dwi laning (2008) stated that juvenile delinquency occurred not from themselves but could occurred from friends mingle, family and the society. So the researcher wants to saw is the parent guidance technique has effect toward juvenile deliquency in kelurahan rejosari tenayan raya districts pekanbaru city. The population was all adolescent in 15-19 years old as much as 2709 person. The research samples was 96 person in 15-19 years old. The research samples technique by using sampling insidental technique with the data collection technique by using observation, questionnire, interview and documentation. The research method using descriptive quantitative , the data analysis using distribution table by relative frequency, and double regression using SPSS 17 version. The research result showed that the parent guidance technique in Kelurahan Rejosari Tenayan Raya districts Pekanbaru city in categorized “good” based on answered result in rare or very rare was at 50,1%-75%. A Juvenile delinquency in Kelurahan Rejosari Kecamatan Tenayan Raya Kota Pekanbaru in categorized “medium” based on interpretation criteria was at 41%-60% from the result of F test based on Anova table via SPSS 17 version that any significant effect between parent guidance technique toward juvenile delinquency by evidence with score of F table was 2,70 while Fhitung was 9,75. A Variable that has significant effect was authoritarian guidance technique variable. A number of contribution or donations of parent guidance variables toward juvenile delinquency showed by a number of R square or coefisien determination (R2) was 0,241. So it can be concluded that parent guidance technique has significant effect 24,1% toward juvenile delinquency in Kelurahan Rejosari Kecamatan Tenayan Raya Kota Pekanbaru, the rest was influenced by variables that was not in carefully.Keywords: The Effect, parent guidance technique, juvenile delinquency.